Analisis Pengaruh Penertiban Pemakaian Tenaga Listrik Terhadap Penurunan Susut Non Teknis pada PT PLN (Persero) ULP Tapaktuan - Repka Cipta Pramudita; Hamdani Hamdani; Rahmaniar Rahmaniar (Pusat riset dan Inovasi Nasional, 2025)
PT PLN (Persero) is a State-Owned Enterprise that provides electricity services to the community. There is an Energy Transaction Section, especially the Loss Control subsection, in this field the main task is to minimize the level of losses that occur at PLN. Large losses can cause large losses to the company. Loss is the loss of electrical energy caused by several factors. Loss is divided into technical losses and non-technical losses. Currently, non-technical losses often occur and contribute quite a large number to PLN's loss data. This loss often occurs due to the actions of several PLN customers themselves who commit violations when using electricity in various ways. There are many types of violations committed by customers when found in the field, one of which is playing with the components on the kWh meter so that this can cause the kWh meter not to calculate energy usage properly and correctly. Of course, this cannot be ignored by the company, therefore at PT. PLN there are also Electricity Usage Control officers. P2TL officers are officers who regulate the use of electricity and ensure that all electricity used is calculated correctly on the kWh meter.